Laser Thomson scattering diagnostics - developments and applications to high-temperature plasmas and plasmas for industrial applications - Muraoka, Katsunori (Вопросы атомной науки и техники, 2006)
Laser Thomson scattering was applied to plasma diagnostics almost as soon as laser was invented in 1960. The most important contribution of the technique to plasma physics and controlled fusion came from the confirmation of good confinement of plasmas in the T-3 tokamak in 1968, by a collaboration of Russian and British physicists. Since then, extensive developments of the technique have been made to meet various measurement requirements, not only in hightemperature plasmas but in plasmas for industrial applications. In this article, these developments are briefly reviewed, followed by the work of the author and its implications for understanding various plasma phenomena.